2022
DOI: 10.35772/ghm.2021.01037
|View full text |Cite
|
Sign up to set email alerts
|

Burden of cancer attributable to modifiable factors in Japan in 2015

Abstract: The structure of disease in Japan has changed drastically over the past decades, largely due to changes in economics, demographics and lifestyle. Together with rapid aging, the transition from communicable diseases such as tuberculosis and pneumonia to noncommunicable diseases such as cancer has challenged domestic health systems and public health.Cancer has been the leading causes of death in Japan since 1981 (1). Recent statistics show that cancer accounted for 27.3% of all deaths (n = 1,381,093) (31.1% of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 50 publications
3
29
2
Order By: Relevance
“…We conducted a cross-sectional nationwide population-based survey in Japan to analyze current awareness of cancer prevention and the association between information sources and health behaviors for cancer prevention. We found that tobacco smoking and cancer-causing viral and bacterial infection were the two highest perceived factors, both of which are major causes of cancer in Japan (16.6% of cancer incidence was explained by infections and 15.2% by active smoking in both sexes in 2015 in a recent analysis) 17 . Furthermore, reliable information sources including health professionals and the websites of public institutions were associated with a broad range of favorable health behaviors, and brochures and advertisements were associated with cancer screening/health check-up and abstinence from smoking and drinking.…”
Section: Discussionmentioning
confidence: 85%
“…We conducted a cross-sectional nationwide population-based survey in Japan to analyze current awareness of cancer prevention and the association between information sources and health behaviors for cancer prevention. We found that tobacco smoking and cancer-causing viral and bacterial infection were the two highest perceived factors, both of which are major causes of cancer in Japan (16.6% of cancer incidence was explained by infections and 15.2% by active smoking in both sexes in 2015 in a recent analysis) 17 . Furthermore, reliable information sources including health professionals and the websites of public institutions were associated with a broad range of favorable health behaviors, and brochures and advertisements were associated with cancer screening/health check-up and abstinence from smoking and drinking.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the 29 preventable behavioural and metabolic risk factors addressed in the GBD 2019, we considered the following five infections, which are known to cause a large burden of disease in cancer patients in Japan, 13 , 14 , 15 as important and preventable cancer risk factors: hepatitis B virus, hepatitis C virus, Helicobacter pylori , human papillomavirus (HPV), and human T-cell leukemia virus type 1 (HTLV-1). Since the GBD 2019 estimated DALYs and deaths from cancer caused by hepatitis B and C, we treated those values as the cancer disease burden attributable to hepatitis B and C virus infection as risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…“Environmental factors” are generally recognized as everything that is not specifically genetic in origin, including tobacco smoking, alcohol consumption, diet and nutrition, infectious agents, radiation, sunlight, exposure to environmental chemicals, and so on. In Japan, the greatest contributing factors to cancer in 2015 were infectious agents and active tobacco smoking, followed by alcohol drinking [ 1 ]. Although attributable fraction might be smaller than for infectious agents and tobacco smoking, exposure to certain chemicals in the environment, at home, and at work may contribute to the risk of developing cancer [ 2 ].…”
Section: Introductionmentioning
confidence: 99%